1996
DOI: 10.1073/pnas.93.6.2408
|View full text |Cite
|
Sign up to set email alerts
|

GSP-1 genes are linked to the grain hardness locus (Ha) on wheat chromosome 5D.

Abstract: An important determinant of wheat grain quality is the hardness of the grain. The trait is controlled by a major locus, Ha, on the short arm of chromosome 5D. Purified starch granules from soft-grained wheats have associated with them 15-kDa polypeptides called grain softness proteins (GSPs) or "friabilins." Genes that encode one family of closely related GSP polypeptides-GSP-1 genes-were mapped using chromosome substitution lines to the group 5 chromosomes. An F2 population segregating for hard and soft allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 20 publications
(41 reference statements)
2
43
0
Order By: Relevance
“…The loci Pina-D1 (Sourdille et al 1996) and Pinb-D1 (Giroux and Morris 1997) were previously mapped to the distal region of chromosome 5DS in dierent mapping populations. The grain softness-related gene Gsp-1 was also mapped on the same region of chromosome 5D of T. aestivum and Aegilops tauschii (Dubcovsky and Dvorak 1995;Jolly et al 1996) and chromosome 5A m of T. monococcum (Dubcovsky et al 1996). This indirect evidence for linkage among the three Ha-related genes was con®rmed here by demonstrating that these three genes are tightly linked in the distal region of the short arm of chromosome 5A m in a single segregating population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loci Pina-D1 (Sourdille et al 1996) and Pinb-D1 (Giroux and Morris 1997) were previously mapped to the distal region of chromosome 5DS in dierent mapping populations. The grain softness-related gene Gsp-1 was also mapped on the same region of chromosome 5D of T. aestivum and Aegilops tauschii (Dubcovsky and Dvorak 1995;Jolly et al 1996) and chromosome 5A m of T. monococcum (Dubcovsky et al 1996). This indirect evidence for linkage among the three Ha-related genes was con®rmed here by demonstrating that these three genes are tightly linked in the distal region of the short arm of chromosome 5A m in a single segregating population.…”
Section: Discussionmentioning
confidence: 99%
“…cDNAs encoding for these proteins have been characterized (Gautier et al 1994;Rahman et al 1994) and mapped on the distal part of chromosome 5DS completely linked to the Ha locus. The Pina-1 and Pinb-1 loci have been detected only on the 5D chromosome but homoeologous Gsp-1 loci were detected on chromosomes 5A, 5B and 5D (Dubcovsky and Dvorak 1995;Jolly et al 1996;Sourdille et al 1996;Giroux and Morris 1997). Though linkage of puroindoline and Gsp-D1 genes to the Ha locus in dierent mapping populations suggests that these genes should be linked, no estimate is available of the genetic distances among these three genes because the limited polymorphism on the D genome of T. aestivum has precluded their study in a common mapping population.…”
Section: Introductionmentioning
confidence: 99%
“…result in high kernel hardness (Giroux et al 2000;Lillemo and Morris 2000;Morris et al 2001;Xia et al 2005;Chen et al 2006;Ram et al 2005). Grain softness proteins (GSPs) are closely related to puroindolines (Gautier et al 2000) and the grain softness protein-1 gene (Gsp-D1) is closely linked to the Ha locus in wheat (Jolly et al 1996) and T. monococcum L. (Gsp-Am1). Despite the close relationship among these three genes, there is no clear evidence of the role of Gsp-1 on grain kernel hardness (Tranquilli et al 2002).…”
Section: Mots Clé S: Triticum Aestivum Durete´du Grain Puroindolinesmentioning
confidence: 99%
“…Friabilin has been found on water-washed starch granules from soft wheat, while little or no friabilin has been found on water-washed starch granules from hard wheat (Greenwell and Scholfield, 1986). It was later shown that genes encoding friabilin were closely linked to the Ha locus on chromosome 5D (Jolly et al, 1996). N-terminal sequencing of friabilin revealed that it is composed mainly of 2 proteins, puroindoline A (PIN A) and puroindoline B (PIN B), which are the main components of friabilin (Jolly et al, 1993;Morris et al, 1994).…”
Section: Introductionmentioning
confidence: 99%